Marketing Concepts of New Housing Projects in Surabaya during Pandemic based on Property Agent Perspective - Miftakhul Huda; Eko Budi Santoso (IPTEK Journal of Proceedings Series, 2023)
The increasing demand and needs of consumers in property transactions makes the need for property agents even greater. In a pandemic condition that limits direct interaction, many housing developers have difficulty selling their housing products due to limited interaction with potential consumers and the lack of up-to-date information on housing products that consumers are interested in during this pandemic. The purpose of this study was to analyze the factors and sequence of criteria that became the basis for selecting new housing during the pandemic based on the perspective of a property agent.This study uses qualitative and quantitative research using interview data and processed into numerical data using product, price, promotion, place, and person variables. The method used is the Delphi method, AHP and Content Analysis, with the Delphi method useful for determining criteria and indicators that are validated from experts and AHP functioning as a weight for the validated criteria. While Content Analysis is used to formulate concepts.The results of this study obtained a sequence of variables that affect Product, (2) Place, (3) Price, (4) Promotion, (5) People.